Cognitive and behavioral heterogeneity in genetic syndromes - Luiz F.L. Pegoraro; Carlos E. Steiner; Eloisa H.R.V. Celeri; Claudio E.M. Banzato; Paulo Dalgalarrondo (Brazilian Society of Pediatrics, 2014)
Objective: this study aimed to investigate the cognitive and behavioral profiles, as well as the psychiatric symptoms and disorders in children with three different genetic syndromes with similar sociocultural and socioeconomic backgrounds. Methods: thirty-four children aged 6 to 16 years, with Williams-Beuren syndrome (n = 10), Prader-Willi syndrome (n = 11), and Fragile X syndrome (n = 13) from the outpatient clinics of Child Psychiatry and Medical Genetics Department were cognitively assessed through the Wechsler Intelligence Scale for Children (WISC-III). Afterwards, a full-scale intelligence quotient (IQ), verbal IQ, performance IQ, standard subtest scores, as well as frequency of psychiatric symptoms and disorders were compared among the three syndromes. Results: significant differences were found among the syndromes concerning verbal IQ and verbal and performance subtests. Post-hoc analysis demonstrated that vocabulary and comprehension subtest scores were significantly higher in Williams-Beuren syndrome in comparison with Prader-Willi and Fragile X syndromes, and block design and object assembly scores were significantly higher in Prader-Willi syndrome compared with Williams-Beuren and Fragile X syndromes. Additionally, there were significant differences between the syndromes concerning behavioral features and psychiatric symptoms. The Prader-Willi syndrome group presented a higher frequency of hyperphagia and self- injurious behaviors. The Fragile X syndrome group showed a higher frequency of social interaction deficits; such difference nearly reached statistical significance. Conclusion: the three genetic syndromes exhibited distinctive cognitive, behavioral, and psychiatric patterns.